If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 = -10 + x Solving -7 = -10 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + -1x = -10 + x + -1x Combine like terms: x + -1x = 0 -7 + -1x = -10 + 0 -7 + -1x = -10 Add '7' to each side of the equation. -7 + 7 + -1x = -10 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -10 + 7 -1x = -10 + 7 Combine like terms: -10 + 7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| X^2+11x+35=5 | | 8P^4*3p= | | 25x-5+10x= | | 2x^4-4x^3-3=0 | | 3-2/2+6=z+8 | | X^2+42X-43=0 | | 7-3x=x-4(2+6) | | b+3=33-b | | 3-9=4x+4 | | x=250+0.8(x-(325+0.25x))+650-80i+560 | | 1x^2-30x=0 | | 6x^2-5x=x | | 4x-12=24+8x | | 11x+12y=150 | | (x^2+7x-48)/(x+9) | | 6x-3(x-4)=2(x+7)+x | | p^2-13p+36=0 | | 4x+16=-12 | | 10-2x=9-5x | | 4(3x-5)=4x+4 | | -3p^3+3p^2+6p=0 | | -2x-14=4(x-2) | | 5(x+2)=-40 | | 3m+3=m-1 | | 3(3x+5)-2x=7x+15 | | 3(x-2)2(x+5)=3(x+1)2(x-1)+3 | | (x+3)(x-3)=(x+6) | | 3a+7a=6 | | 2x+10+3x=-12--20 | | 8/7+x+5/7+x | | t^2=4t+3 | | -2x^2+6x-2=-3 |